2014
DOI: 10.1167/iovs.13-13461
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ataxia Telangiectasia Mutated (ATM) Kinase Suppresses Herpes Simplex Virus Type 1 (HSV-1) Keratitis

Abstract: This study identifies ATM as a potential target for the treatment of HK. ATM inhibition by KU-55933 reduces epithelial infection and stromal disease severity without producing appreciable toxicity. These findings warrant further investigations into the DNA damage response as an area for therapeutic intervention in herpetic ocular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
2
24
1
Order By: Relevance
“…Work is continuous, but it appears that promising opportunities are being identified. Alekseev et al 203 have recently identified a kinase, ataxia telangiectasia mutated (ATM) kinase, whose inhibition reduces the severity of keratitis in a mouse model of HSV1 keratitis and additionally slows viral replication in rabbit and human cultured corneas. A high-affinity human monoclonal antibody to S. aureus α-toxin has been found to be effective at reducing corneal damage 204 and a new antibiotic, targocil, has had some preliminary success at inhibiting the severity of staphylococcal infections.…”
Section: Potential Targeted Molecular Therapiesmentioning
confidence: 99%
“…Work is continuous, but it appears that promising opportunities are being identified. Alekseev et al 203 have recently identified a kinase, ataxia telangiectasia mutated (ATM) kinase, whose inhibition reduces the severity of keratitis in a mouse model of HSV1 keratitis and additionally slows viral replication in rabbit and human cultured corneas. A high-affinity human monoclonal antibody to S. aureus α-toxin has been found to be effective at reducing corneal damage 204 and a new antibiotic, targocil, has had some preliminary success at inhibiting the severity of staphylococcal infections.…”
Section: Potential Targeted Molecular Therapiesmentioning
confidence: 99%
“…Since the original discovery that placed this kinase within the host DNA damage response network, ATM has been recognized as a key player in several additional cellular signaling networks that include oxidative stress, metabolism, angiogenesis, and mitophagy (reviewed in (Guleria & Chandna, 2016)). Intriguingly, this kinase also supports replication of multiple diverse DNA and RNA viruses, including but not limited to human and mouse gammaherpesviruses (Hagemeier, Barlow et al, 2012; Singh, Dutta et al, 2013; Tarakanova, Leung-Pineda et al, 2007), alpha- and beta herpesviruses (E X, Pickering et al, 2011; Alekseev, Donovan et al, 2014), papilloma- and polyomaviruses (Moody & Laimins, 2009; Tsang, Wang et al, 2014; Jiang, Zhao et al, 2012), adenovirus (Shah & O’Shea, 2015), HCV (Ariumi, Kuroki et al, 2008), and HIV (Lau, Swinbank et al, 2005). The functions of ATM in the DNA damage response have traditionally been assumed as the mechanism underlying the proviral activity of this kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular DDR proteins are also possible candidates for treatment of acute HSV-1 infection. For example, the ATM inhibitor, KU-55933 has recently been shown to suppress HSV-1 replication and cytopathic effects in herpes keratitis [112]. The observation that several DDR proteins are important antiviral modulators may also be exploited in the future for novel antiviral strategies.…”
Section: The Future Outlook Of Hsv-1 and Cellular Ddr Researchmentioning
confidence: 99%